Mothers' Weaning Practices when Infants Breastfeed for More Than One Year. Issue 2 (March 2017) - Cunniff, Addie; Spatz, Diane
Abstract : Abstract: The American Academy of Pediatrics and the World Health Organization recommend that infants receive human milk exclusively for the first 6 months of life and that breastfeeding continue beyond the first or second year of life for as long as a family deems appropriate. More infants in the United States and around the world are meeting this recommendation. As more infants breastfeed beyond the first year of life, best practices for weaning toddlers come into question. Little is known about concerns and practices of breastfeeding mothers weaning their children from feedings. Current evidence on weaning from an evolutionary, social, and practical perspective is presented. Four case exemplars are provided to illustrate complexities of weaning. Implications for practice and suggestions for future research are provided. Abstract : Not much is known about weaning from breastfeeding after the baby is a year old or more. The literature has not been updated for over a decade. A summary of current issues and four exemplar cases of weaning after extended breastfeeding are presented.